Podmiotowość jako transcendencja. Przyczynek do definicji podmiotowości politycznej - Paradowska, Wiera; Paradowski, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
To define political subjectiveness as a purpose-oriented activity brings about the obliteration of differences between authoritarian policy and liberal-and-democratic policy, as well as between an authoritarian and liberal-and-democratic definition of politics. The authors of the paper considered it justified to move from the common comprehension of subjectiveness to its metaphysical aspect, and to positioning it in the realm of philosophical transcedency. This required them to determine the difference between a philosophical and religious meaning of tanscendency. This difference is demonstrated in the article.